Ketegaran Upah Nominal sebagai Sarana Rekonsiliasi Hubungan Industrial pada Masa Krisis - Susanto, Joko (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
The decreasing of worker productivity, that happened in the crisis, would be a reason for employer to lower nominal wages. However, the crisis also led to a reduction of worker's real incomes due to higher inflation so the workers ask higher nominal wage to maintain their welfare. This research analysis nominal wage determination in Indonesian chemical industries during the crisis. This research uses regression analysis based on the dynamic panel data model. The results show that during the crisis, nominal wage rate is not decrease. Employer state that decline in nominal wage have a negative impact on company performance. During the crisis, downward nominal wage rigidity is a way for industrial relations reconciliation.